Homework Help

Factor. A) x^2-4x+3 B)x^2+5x-24

user profile pic

shawnwifey16 | Student, Undergraduate | (Level 2) Honors

Posted April 27, 2013 at 11:58 AM via iOS

dislike 1 like

Factor. A) x^2-4x+3 B)x^2+5x-24

5 Answers | Add Yours

user profile pic

pramodpandey | College Teacher | (Level 3) Valedictorian

Posted April 27, 2013 at 12:13 PM (Answer #1)

dislike 1 like

We have given

A.  `x^2-4x+3`

factorise 3 as 3.1

`3=3xx1`

`x^2-(3+1)x+3`

`=x^2-3x-x+3`

`` `=x(x-3)-1(x-3)`

`=(x-3)(x-1)`     ( brackets are equal so factor out )

`B. x^2+5x-24`

`we write 24=8xx3`

`x^2+(8-3)x-24`  ,

in bracket we take minus because last term has minus sign.

`=x^2+8x-3x-24`

`=x(x+8)-3(x+8)`

`=(x+8)(x-3)`   (brackets are same so factor out)

user profile pic

spompeo4 | (Level 1) eNoter

Posted April 27, 2013 at 2:05 PM (Answer #2)

dislike 1 like
A. (x-3)(x-1) b. (x+8)(x-3)
user profile pic

oldnick | (Level 1) Valedictorian

Posted April 27, 2013 at 11:59 PM (Answer #3)

dislike 1 like

`A)`    `x^2-4x+3`      find soluton of  `x^2-4x+3=0`

`Delta= 16-4(3)=4>0`  has two solution

`x=(4+-sqrt(4))/2=(4+-2)/2`     `x_1=3`     `x_2= 1`

The poliniom is decomponed in:

     `(x-x_1)(x-x_2)= (x-1)(x-3)`

``

user profile pic

oldnick | (Level 1) Valedictorian

Posted April 28, 2013 at 12:12 AM (Answer #4)

dislike 1 like

`B)`   `x^2+5x-24=0`

`Delta= 25-4(-24)=121>0`   Two real different solutions.

`x=(-5+-sqrt(121))/2=(-5+-11)/2`

`x_1=3`    `x_2=-8`

`x^2+5x-24=(x-3)(x+8)`

user profile pic

atyourservice | Student, Grade 10 | (Level 3) Valedictorian

Posted April 19, 2014 at 8:11 PM (Answer #5)

dislike 0 like

 A) `x^2-4x+3`

use the a x c method

find factors of the product (3) that add up to b (-4) which would be -1 and -3 plug them in as b

`x^2-x-3x+3 `

group

`(x^2-x)(-3x+3) `

factor out he greatest common factor

x(x-1) -3(x-1)

(x-3) (x-1)

x=3  x=1

B)x^2+5x-24

follow the same steps here

find factors of -24 that add up to b (5) which would be 8 and -3

plug them in as b

`x^2+8x-3x-24 `

group 

`(x^2+8x)(-3x-24)  `

x(x+8) -3(x+8)

(x-3)(x+8)

x=3   x=-8

Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes